2021
DOI: 10.3390/cancers13020213
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Response and Immune System Activity during Treatment with Nivolumab in Hepatocellular Carcinoma: Results from a Single-Institution Retrospective Analysis

Abstract: Treatment of hepatocellular carcinoma (HCC) is rapidly evolving, with many new therapeutic options; in particular, immunotherapy (IT) is acquiring a major role, even in combination regimens. Despite these promising results, an important limitation is the lack of prognostic and predictive factors that prevent provision of a tool for patient stratification in order to select the most appropriate strategy. Furthermore, response assessment can be challenging with IT due to peculiar patterns such as mixed responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Organ-specific ORRs for liver, lung, lymph node, and other metastases were 10.1%, 24.3%, 37.14%, and 14.6%, respectively. 6 Rapposelli et al 7 reported different response pattern based on the site of the lesion among 10 patients with HCC treated with nivolumab. CR was observed in two pulmonary lesions (100%) and heterogeneous response in the liver (2 CR, 20 SD, 9 PD; 6%, 65%, 29%, respectively) (RECIST) and other organ lesions (2 PR, 1 SD, 5 PD; 25%, 12.5%, 62.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ-specific ORRs for liver, lung, lymph node, and other metastases were 10.1%, 24.3%, 37.14%, and 14.6%, respectively. 6 Rapposelli et al 7 reported different response pattern based on the site of the lesion among 10 patients with HCC treated with nivolumab. CR was observed in two pulmonary lesions (100%) and heterogeneous response in the liver (2 CR, 20 SD, 9 PD; 6%, 65%, 29%, respectively) (RECIST) and other organ lesions (2 PR, 1 SD, 5 PD; 25%, 12.5%, 62.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…8 Liver lesions in HCC are associated with an immunosuppressive microenvironment. 7 T-cell exhaustion, immune dysfunction, and high levels of immunosuppressive molecules comprise the immunosuppressive features of the liver microenvironment. In patients with melanoma and NSCLC, liver metastases characterized by reduced CD8+ T-cell infiltration further show the immunosuppressive microenvironment of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…PsP can occur not only in existing target lesions but also in new lesions. For instance, Rapposelli et al 123 observed PsP in bone metastasis (rather than the primary lesions) in a patient with HCC. Similarly, Sangro et al 117 reported the growth of nontarget lesions (tumors in the lung, left iliac crest, and pelvic lymph nodes) in HCC patients following therapy with atezolizumab plus bevacizumab, as assessed by computed tomography (CT).…”
Section: Manifestations Of Pspmentioning
confidence: 99%
“…A handful of biomarkers are currently identified to be associated with an improved survival and response in nivolumab treatment, such as PD-1 and PD-L1 expression, 141 , 149 a good AFP response, 150 inflammatory cytokines (CD3 and CD8) 149 and peripheral blood mononuclear cells (effector T cells and nonclassical monocytes). 151 This algorithm remains yet to be confirmed in some large prospective studies.…”
Section: Treatment Advances In Systemic Therapymentioning
confidence: 99%